Effect of heat and relative humidity treatment on γ‐aminobutyric acid accumulation, other micronutrients contents, antioxidant activities and physicochemical properties of mung bean (Vigna radiata L.). (13th November 2021) - Ma, Yuling; Tong, Litao; Wang, Shanshan; Liu, Tingyu; Wang, Lili; Liu, Liya; Zhou, Xianrong; Zhou, Sumei; Blecker, Christophe
Summary: A novel approach to heat and relative humidity (HRH, 65‐75 °C, 98% RH) treatment was used to enhance γ‐aminobutyric acid (GABA) of mung bean with a low moisture (12‐20%) within several hours (4‐6 h). Meanwhile, the changes in micronutrients, antioxidant activities and physicochemical properties were also evaluated. Results showed that the GABA content was significantly accumulated, increasing from 1.73 to 109.78 mg 100 g −1 dry weight (DW) under the conditions of 16.72% moisture, 68.97 °C, 98% RH for 5.34 h. Meanwhile, the amino acids, including aromatic (tyrosine and phenylalanine), sulphur‐containing (methionine and cystine) and branched‐chain amino acids (leucine, isoleucine and valine), were significantly increased ( P < 0.05). Although HRH treatment decreased the total anthocyanin content of mung bean, the total phenolic, vitexin and isovitexin contents, and antioxidant activities were significantly increased ( P < 0.05). Furthermore, HRH treatment caused the wrinkled structure of mung bean coat, increased the paste viscosity of mung bean flour and decreased the time of complete gelatinisation of starch in mung bean by one third during cooking. These results suggested that HRH treatment could effectively elevate the above functional components, especially GABA, improve the antioxidant activities, pasting and cooking properties of mung bean. Abstract : The graphical abstract of GABA accumulation and the changes of physicochemical properties under heat and relative humidity treatment.